2014
DOI: 10.1128/aem.03477-13
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Growth of Dehalococcoides mccartyi 195 by Corrinoid Salvaging and Remodeling in Defined Lactate-Fermenting Consortia

Abstract: dCorrinoids are essential cofactors of reductive dehalogenases in Dehalococcoides mccartyi, an important bacterium in bioremediation, yet sequenced D. mccartyi strains do not possess the complete pathway for de novo corrinoid biosynthesis. Pelosinus sp. and Desulfovibrio sp. have been detected in dechlorinating communities enriched from contaminated groundwater without exogenous cobalamin corrinoid. To investigate the corrinoid-related interactions among key members of these communities, we constructed consort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 48 publications
5
55
0
Order By: Relevance
“…However, the mechanisms that regulate the activity of D. mccartyi within natural ecosystems and shape its functional robustness in disturbed environments are poorly understood due to multiscale microbial community complexity and heterogeneity of biogeochemical processes involved in the sequential degradation (3,4). D. mccartyi exhibits specific restrictive metabolic requirements for a variety of exogenous compounds, such as hydrogen, acetate, corrinoids, biotin, and thiamine, which can be supplied by other microbial genera through a complex metabolic network (1,(5)(6)(7)(8). Therefore, the growth of D. mccartyi is more robust within functionally diverse microbial communities that are deterministically assembled than in pure cultures (5,8,9).…”
mentioning
confidence: 99%
“…However, the mechanisms that regulate the activity of D. mccartyi within natural ecosystems and shape its functional robustness in disturbed environments are poorly understood due to multiscale microbial community complexity and heterogeneity of biogeochemical processes involved in the sequential degradation (3,4). D. mccartyi exhibits specific restrictive metabolic requirements for a variety of exogenous compounds, such as hydrogen, acetate, corrinoids, biotin, and thiamine, which can be supplied by other microbial genera through a complex metabolic network (1,(5)(6)(7)(8). Therefore, the growth of D. mccartyi is more robust within functionally diverse microbial communities that are deterministically assembled than in pure cultures (5,8,9).…”
mentioning
confidence: 99%
“…However, to our knowledge, these taxa are not known to provide the more important organic cofactors such as vitamin B12 needed by Dcm, hence they are not likely "sufficient" as companions to sustain Dcm growth. In line with this, other studies showed the importance of particular syntrophic partners belonging to Firmicutes and Deltaproteobacteria in providing the "right" cobamide lower base of vitamin B12 that is vital for Dcm dechlorination [95,300] but cannot be provided even by closely related microbes [93,299].…”
Section: Discussionsupporting
confidence: 55%
“…The most dynamic period was after day 72 during which the average  Table S6.6) is likely due to their glycerol fermentation capacity [408][409][410][411]. Moreover, Pelosinus strains were shown to sustain growth of Dcm by providing the necessary corrinoids [95,300].…”
Section: Geochemical and Microbial Dynamics: Post-biostimulation Phasementioning
confidence: 99%
“…With regard to cobalamin, bacteria in consortia are known to remodel corrinoids obtained from other species, 37 however, studies on algae are limited. One recent study has shown that some eukaryotic algae can convert pseudocobalamin into cobalamin when provided with 5,6-dimethylbenzimidazole.…”
Section: Discussionmentioning
confidence: 99%